Exuberant Rice Body Formation Associated with Adverse Local Tissue Reaction After Hip Resurfacing Arthroplasty: A Case Report and Review of the Literature. Issue 2 (13th April 2023) - Ramirez, Daniel C.; Ren, Renee; Burge, Alissa J.; Potter, Hollis G.; Su, Edwin; Bauer, Thomas W.
Abstract : Case: A 65-year-old man with osteoarthritis of the hip developed a soft-tissue mass of the inferior gluteal region 3 years after metal-on-metal resurfacing hip arthroplasty. Clinical and imaging findings suggested an adverse local tissue reaction. Intraoperatively, nearly 1 liter of intra-articular fibrinous loose bodies (rice bodies) was removed, and histology showed features of an adaptive immune response. The patient had no evidence of an autoimmune disease or mycobacterial infection. Conclusion: To our knowledge, this is the first reported case of florid rice bodies associated with a metal-on-metal hip arthroplasty and adverse local tissue reaction.